Country Partnership Framework for the Federal Democratic Republic of Ethiopia for the Period FY18-FY22 - World Bank; International Finance Corporation; Multilateral Investment Guarantee Agency (World Bank, Washington, DC, 2017)
Ethiopia has achieved substantial progress in economic, social, and human development over the past decade. The country partnership framework (CPF) draws on the findings of the World Bank Group (WBG’s) 2016 systematic country diagnostic (SCD) for Ethiopia, which identified eight binding constraints to ending extreme poverty and boosting shared prosperity, along with two overarching challenges: the need for a sustainable financing model for growth, and inadequate feedback mechanisms to facilitate citizen engagement and government account- ability. This CPF succeeds the Ethiopia FY13-FY16 country partnership strategy (CPS), which was discussed at the Board on August 29, 2012. It also reflects lessons learned and resulting suggestions from the CPS completion and learning review (CLR), which is presented in this report. Following a decade of strong economic growth in Ethiopia, the CPF addresses the challenges of forging a growth path that is more broadly inclusive and sustainable. The CPF program will focus on: (i) promoting structural and economic transformation through increased productivity; (ii) building resilience and inclusiveness (including gender equality); and (iii) supporting institutional accountability and confronting corruption. This CPF adopts a spatial lens through which this five-year program will seek to deliver bold results and to tackle two of the greatest spatial challenges to Ethiopia’s quest to achieve lower middle-income status by 2025.